2017
DOI: 10.5539/apr.v9n6p58
|View full text |Cite
|
Sign up to set email alerts
|

Can the Planck Length Be Found Independent of Big G?

Abstract: In this paper we show how it is possible to measure the Planck length through a series of different methods. One of these measurements is totally independent of big G, but moving from the theoretical realm to the empirical realm would require particle accelerators far more powerful than the ones that we have today. However, a Cavendish-style experiment can also be performed to find the Planck length with no knowledge of the value of big G. Furthermore, the Cavendish style set-up gives half of the relative meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 6 publications
2
43
0
Order By: Relevance
“…Had the Planck length even been different by 10%, then this would change the gravitational constant by 20%. Haug [5] has recently shown that the measurement error in the Planck length is exactly half of that of the gravitational constant. This is based on the assumption that the Planck length represents something fundamental that plays a central role in the quantum world and that gravity itself is ultimately affected by the Planck scale, even at the cosmic scale.…”
Section: The Speed Of Gravity Hidden Within Newton's Gravitational Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Had the Planck length even been different by 10%, then this would change the gravitational constant by 20%. Haug [5] has recently shown that the measurement error in the Planck length is exactly half of that of the gravitational constant. This is based on the assumption that the Planck length represents something fundamental that plays a central role in the quantum world and that gravity itself is ultimately affected by the Planck scale, even at the cosmic scale.…”
Section: The Speed Of Gravity Hidden Within Newton's Gravitational Fomentioning
confidence: 99%
“…An alternative is to try to define the maximum acceleration based on the Heisenberg uncertainty principle, And nothing with rest-mass can travel at the speed of light as this would lead to infinite kinetic energy, which was first pointed out by Einstein [20]. Haug [21] has recently suggested the Planck acceleration only can happen for a Planck mass particle and that this particle then only can last for one Planck second before dissolving into pure energy. This would at least be consistent with a mass accelerated to the speed of light, where the mass is no longer a mass but rather becomes energy.…”
Section: Gravitational Acceleration Fieldmentioning
confidence: 99%
“…By re-formulating G as a composite of the form G = 5. The Planck mass and the Planck length can be measured totally independent of any knowledge of the Newton gravitational constant, as recently shown by Haug [9,10]. This means the elements of a Newtonian composite gravitational constant all are known.…”
Section: When We Understand That the Newton Gravitationalmentioning
confidence: 78%
“…Haug [15] has, in a similar way, shown how the Planck length can be found independent of big G, but his derivation did not start out with the McCulloch-Heisenberg Newton equivalent gravity theory, so we think the derivation and discussion in this paper offer important additional insight. See also Appendix A.2, on how we can extend the derivation above using the McCullochHeisenberg gravity to find the Planck length and Planck time "directly" from a Cavendish apparatus.…”
Section: The Planck Mass Measured Directly From Mcculloch's Derivmentioning
confidence: 99%